Cost‐effectiveness of carbon‐ion radiotherapy versus stereotactic body radiotherapy for non‐small‐cell lung cancer. Issue 2 (6th December 2021) - Okazaki, Shohei; Shibuya, Kei; Takura, Tomoyuki; Miyasaka, Yuhei; Kawamura, Hidemasa; Ohno, Tatsuya
Abstract: Carbon‐ion radiotherapy (CIRT) for clinical stage I non‐small‐cell lung cancer (NSCLC) is used as an advanced medical treatment regimen in Japan. Carbon‐ion radiotherapy reportedly aids in achieving excellent treatment outcomes, despite its high medical cost. We aimed to compare CIRT with stereotactic body radiotherapy (SBRT) in terms of cost‐effectiveness for treating clinical stage I NSCLC. Data of patients with clinical stage I NSCLC treated with CIRT or SBRT at Gunma University between 2010 and 2015 were analyzed. The CIRT and SBRT groups included 62 and 27 patients, respectively. After propensity‐score matching, both groups comprised 15 patients. Life year (LY) was used as an indicator of outcome. The CIRT technical fee was 3 140 000 JPY. There was no technical fee for the second CIRT carried out on the same organ within 2 years. The incremental cost‐effectiveness ratio (ICER) was calculated by dividing the incremental cost by the incremental LY for 5 years after treatment. Sensitivity analysis was applied to evaluate the impact of LY or costs of each group on ICER. The ICERs were 7 491 017 JPY/LY and 3 708 330 JPY/LY for all patients and matched patients, respectively. Hospitalization and examination costs were significantly higher in the CIRT group, and the impact of the CIRT technical costs was smaller than other costs and LY. Carbon‐ion radiotherapy is a cost‐effective treatment approach. However, our findings suggest that reducing excessive costs by considering the validity and necessity of examinations and hospitalizations would make CIRT a more cost‐effective approach. Abstract : This single‐institutional retrospective study evaluated the cost‐effectiveness of carbon‐ion radiotherapy (CIRT) compared with stereotactic body radiotherapy (SBRT) for clinical stage I non‐small‐cell lung cancer (NSCLC) from the economic standpoint of cost‐effectiveness. Carbon‐ion radiotherapy for clinical stage I NSCLC is used as advanced medical treatment in Japan and entails expensive medical costs, although it achieves excellent treatment outcomes. The actual measurement‐based cost‐effectiveness analysis and sensitivity analysis showed that the impact of the CIRT technical costs was relatively smaller, and CIRT was a cost‐effective treatment.